Politics as Radical Creation : Herbert Marcuse and Hannah Arendt on Political Performativity - Holman, Christopher (Book collections on Project MUSE., 2013)
Politics as Radical Creation examines the meaning of democratic practice through the critical social theory of the Frankfurt School.